Designing multi-function rapid right angle set slurry compositions for a high pressure-high temperature well - Pooria Kianoush; Mostafa Gomar; Nasser Keshavarz Faraj Khah; Seyednooroldin Hosseini; Ali Kadkhodaie; Shahaab Varkouhi (Results in Earth Sciences)
Cementing in high-pressure-high-temperature (HPHT) wells presents challenges due to gas penetration into the cement, leading to low bonding quality and well isolation failures. This study aimed to design a novel multi-target cement formula to deter gas penetration and prevent complications such as formation creep and cement deterioration. A cement slurry was developed for two liner intervals in the first exploratory well in the Minoo field, SW Iran, at a depth of over 6000 m. The thermal gradient was 1.62 °F/100 ft, significantly impacting cement performance; elevated temperatures can accelerate hydration reactions, potentially causing strength retrogression. A blend of additives—including 3 % boric acid as a dual-functioning dispersant and 1 % latex materials—enhanced dispersing properties, compressive strength, and gas migration resistance. The designed slurry achieved an API fluid loss of 4.5 cc and 15 cc, transition times (30BC to 70BC) under 1 minute, with compressive strengths of 25.29 MPa and 35.44 MPa, respectively, compared to ordinary slurries that typically exhibited fluid losses greater than 50 cc and lower strengths. Gas migration resistance was analyzed through fluid migration tests, showing a 50 % reduction in permeability with silica nanoparticles. CBL/VDL logging data confirmed effective bonding and isolation in the wellbore. The innovative formulation enhances the mechanical properties of the cement—improving its durability and ensuring long-term stability in extreme conditions—while also addressing gas migration challenges. This study advances cement technology, enhancing the performance and reliability of cement-based materials in extreme environments through innovative methods, including using boric acid and latex materials in HPHT cement compositions.